The Relationship between Corporate Legal Compliance and Public Service Quality in the Public Sector: A Literature Review - Adi Saputra; Pandri Zulfikar; Ibrahim Aji; Mahfudlon Mahfudlon; Yusfika Ely Nur Afifah; Dian Wibowo (Citakonsultindo, 2026)
This study explores the relationship between corporate legal compliance and public service quality in the public sector through a systematic literature review approach. Legal compliance is recognized as a fundamental element of good governance, ensuring that public institutions operate within regulatory frameworks that promote accountability, transparency, and fairness. At the same time, public service quality reflects the effectiveness of government institutions in meeting citizens’ expectations, often measured through dimensions such as reliability, responsiveness, assurance, empathy, and tangibility. The findings of this review indicate that legal compliance plays a significant role in shaping service quality by establishing standardized procedures, reducing risks of maladministration, and enhancing institutional trust. However, the relationship is not purely linear, as it is influenced by organizational factors such as leadership, institutional culture, human resource capacity, and the integration of digital technologies. While compliance mechanisms such as audits and regulatory controls improve procedural accountability, they may not always guarantee improved service outcomes if applied rigidly. This study concludes that legal compliance is a necessary but insufficient condition for achieving high-quality public services. A balanced approach that combines regulatory adherence with flexibility, innovation, and citizen-centered practices is essential. Future research is encouraged to develop integrative models and empirical analyses to strengthen the linkage between compliance and service quality. Keywords : Legal Compliance; Public Service Quality; Governance; Public Sector